Experimental evaluation and numerical verification of enhanced heat transportation by using ultrasonic assisted nanofluids in a closed horizontal circular passage. (August 2021) - Ahmed, Waqar; Chowdhury, Z.Z.; Kazi, S.N.; Bin Johan, Mohd. Rafie; Abdelrazek, Ali H.; Fayaz, H.; Badruddin, IrfanAnjum; Mujtaba, M.A.; M Soudagar, Manzoore Elahi; Akram, Naveed; Mehmood, Shahid; Ahmad, Muhammad Shakeel; et al.
Abstract: In the current study, the ratio of a precise heat transfer growth to the different wt.% of the Zinc oxide-DW (ZnO-DW) based nanofluids are considered in a closed single-tube circular heat exchanger experimentally and by using ANSYS modeling. Four varying concentrations, 0.1%, 0.075%, 0.05%, and 0.025% wt. of the ZnO-DW nanofluids were considered and their thermal and hydrodynamic characteristics were determined experimentally and numerically. The experiments were conducted with base fluid (distilled water) as a working fluid for the validation of the 2-D numerical model. Using ANSYS-Fluent, a 2-dimensional domain was constructed and k-ϵ turbulent model was utilized to evaluate the continuity, energy, and momentum equations. All the nanofluids were experimentally and numerically examined with Reynolds (Re) numbers ranging from 5849 to 24544 and then validated using empirical correlations. Reynolds (Re) number, heat transfer coefficient, and Nusselt number were calculated and analyzed. The highest pressure drop was noticed for 0.1 wt% which is about 11184.9 m.Pas, while the highest friction (f) was 0.072983. Similarly, the maximum average heat transfer coefficient (h) and average Nusslet numbers ( Nu ) were been calculated both numerically and experimentally. At the highest 0.1 wt%. concentration of the ZnO-DW based nanofluids the supreme heat transfer was recorded about 13799.50 W/m 2 .K (71%) and the average Nusselt numbers ( Nu ) were noticed 176.47 (67.3%). Both experimental and ANSYS modeling results reflected that the 0.1% ZnO-DW based nanofluids contributed the highest heat transfer coefficient with an overall average deviation up to ±9.2%. Both experimental and numerical results showed promising and similar outcomes. Graphical abstract: Image 1 Highlights: The ZnO nanoparticles were synthesized by using the facile sonochemical technique. The 2-step facile ultrasonic assisted technique was used to prepare varying wt.% of ZnO-DW nanofluids. The experiment was conducted for friction (f), pressure drop, and Heat transfer coefficient. Numerical (ANSYS) simulation was conducted for heat transfer growth to the ZnO-DW nanofluids. A comparison study was comprehended between experimental and ANSYS results.